SPATIAL ANALYSIS OF LAND USE CHANGE DUE TO MINING ACTIVITIES IN KALUMATA VILLAGE, SOUTH TERNATE DISTRICT (2014–2024) - Amrih Halil; Nurany (Acceleration: Multidisciplinary Research Journal, 2025)
The mining area in Ternate City is generally a mining business for rock excavation materials, which is found in almost all areas of Ternate city, one of which is in Kalumata Village, South Ternate District. This study investigates land use change in the mining area of Kalumata Village, South Ternate District, from 2014 to 2024, using Geographic Information System (GIS) and Landsat 8 imagery. Mining activities in this area are predominantly carried out by the local community without official permits, leading to uncontrolled land conversion. The study classifies land use into six categories in 2014 and seven in 2024, with the addition of a mining land class. The results show a significant increase in residential areas (28.01 ha) and mixed gardens (3.22 ha), along with the emergence of 5.95 ha of mining land. Conversely, plantation land decreased by 23.24 ha, while forest areas declined by 1.1 ha. These changes are primarily driven by rapid urban development and expanding mining operations. The findings highlight the urgent need for spatial planning and land management strategies to mitigate environmental degradation in Ternate City.